AMICO galaxy clusters in KiDS-DR3: galaxy population properties and their redshift dependence. Issue 3 (7th September 2020) - Radovich, Mario; Tortora, Crescenzo; Bellagamba, Fabio; Maturi, Matteo; Moscardini, Lauro; Puddu, Emanuella; Roncarelli, Mauro; Roy, Nivya; Bardelli, Sandro; Marulli, Federico; Sereno, Mauro; Getman, Fedor; et al.
ABSTRACT: A catalogue of galaxy clusters was obtained in an area of 414 $\deg ^2$ up to a redshift z ∼ 0.8 from the Data Release 3 of the Kilo-Degree Survey (KiDS-DR3), using the Adaptive Matched Identifier of Clustered Objects (amico ) algorithm. The catalogue and the calibration of the richness–mass relation were presented in two companion papers. Here, we describe the selection of the cluster central galaxy and the classification of blue and red cluster members, and analyse the main cluster properties, such as the red/blue fraction, cluster mass, brightness, and stellar mass of the central galaxy, and their dependence on redshift and cluster richness. We use the Illustris-TNG simulation, which represents the state-of-the-art cosmological simulation of galaxy formation, as a benchmark for the interpretation of the results. A good agreement with simulations is found at low redshifts ( z ≤ 0.4), while at higher redshifts the simulations indicate a lower fraction of blue galaxies than what found in the KiDS-amico catalogue: we argue that this may be due to an underestimate of star-forming galaxies in the simulations. The selection of clusters with a larger magnitude difference between the two brightest central galaxies, which may indicate a more relaxed cluster dynamical status, improves the agreement between the observed and simulated cluster mass and stellar mass of the central galaxy. We also find that at a given cluster mass the stellar mass of blue central galaxies is lower than that of the red ones.